Les images des passions adolescentes: Des photographies d'expression faciale aux images scans dans la construction d'un cerveau adolescent émotionnel et sexué - Gumy, Christel (Revue d'anthropologie des connaissances, 2013)
Les recherches en neurosciences utilisant des sets de photographies d’expression faciale afin de tester, à l’aide des techniques d’imageries, les réactions émotionnelles des adolescent-e-s ont participé à établir un modèle neurobiologique de l’adolescence. Ce modèle, qui postule que la configuration cérébrale particulière à cette période de la vie soumet les jeunes personnes à un déficit de contrôle émotionnel, tend à s’imposer dans le domaine des sciences de l’adolescence, particulièrement en lien avec la question des prises de risque. Cet article propose d’investiguer le processus par lequel les neurosciences cognitives ont produit, à partir de portraits photographiques d’acteurs mimant des émotions, des stimuli valides qui permettent de rendre visible par le biais de l’IRMf une différence cérébrale discriminant d’une part 590 les adolescent-e-s et les adultes et d’autre part les jeunes filles et les jeunes garçons dans la gestion de l’information émotionnelle. En effet, le cerveau émotionnel adolescent est construit selon deux hiérarchies enchâssées : si la différence d’âge fait figure de hiérarchie fondatrice, celle de sexe constitue un élément tantôt moteur tantôt modérateur à l’intérieur de celle-ci.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; discipline; nouvelle-guinée; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; soc2051; sociologie; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

Bousso : maternité et bipolarité - Tant que je serai Noire
Tant que je serai Noire c'est le podcast qui répond à la question Tant que je serai Noire, serai-je mère ? Tant que je serai Noire ce sont des récits de femmes qui nous parlent de leur désir ou non désir d'enfant. Un Podcast qui nous montrent à quel point les récits des femmes interrogées st aussi intéressants que les 1000 vies de Maya Angelou. Je suis Tsippora la créatrice et productrice de Tant que je serai Noire. Retrouvez un lundi sur 2 un épisode. *** 📣 Pour cet épisode, je reçois Bousso, professeur d'anglais, co-créatrice du podcast @femigrantespodcast et maman. ❤ Avec Bousso nous avons parlé de maternité et bipolarité. ❤ De la découverte de sa bipolarité ❤ Des circonstances dans lesquelles elle a été enceinte ❤ De la découverte de sa nouvelle relation de mère avec sa fille ❤ De l'équilibre que cette relation lui a apporté 🤎 Quelle belle rencontre pleine de conseils, de rires. Merci à Alice et Agnès pour le montage et pour les illustrations. Le blog de Bousso : Mamma.donnanera
Keywords: 2000 à aujourd'hui; afrique; cours; europe; fem3300; femmes* noires; france; maternité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; santé; santé mentale; sénégal; thématiques